A case report of thrombosed varicosities of pubic collateral veins: Ideal treatment strategy and contribution of era imaging technologies in diagnosis. (9th February 2018) - Paramythiotis, Daniel; Goulas, Patroklos; Bangeas, Petros; Giannopoulos, Argiris; Kapoulas, Kostantinos; Rafailidis, Vasileios; Papadopoulos, Georgios; Ktenidis, Kiriakos; Kalogera-Fountzila, Anna; Michalopoulos, Antonis
Collateral circulation is an alternative path occurring in case of venous or artery obstruction. This path may usually develop after primary recanalization. In our case, a 62-year-old woman presented to our Emergency Department complaining about a suprapubic swelling with a cyanotic discoloration of the overlying skin for the past 10 days for which she had been previously prescribed antibiotics. Investigation with ultrasound and contrast-enhanced computed tomography was performed. An imaging study revealed thrombosed pubic varicose collateral veins due to deep vein obstruction and occlusion of the left external iliac vein. The patient was treated with low-molecular-weight heparin, and swelling subsided gradually. Collateral veins of the abdominal wall and over the pubic tubercle are highly predictive of deep venous obstructive disease proximal to the groin level. These collaterals should never be removed, and the patient should be subjected to a diligent laboratory and imaging investigation.